PKMS PENINGKATAN KOMPETENSI GURU DAN PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS IT GUNA MENUNJANG PELAKSANAAN KURIKULUM 2013 PADA SMP NEGERI 1 ANJIR PASAR DESA ANJIR PASAR KOTA II KEC. ANJIR PASAR KAB. BATOLA - Agus Alim Muin; Sari Kumala; Erfan Karyadiputra (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
The development of information and communication technology in the world of education, especially in the learning process, requires teachers to develop learning innovations by utilizing this information technology function in planning, implementing, and evaluating learning. The ability of teachers as professional educators must be able to follow the development of science and technology in an effort to improve competence and quality in teaching in the face of the implementation of the 2013 curriculum. Most of the teachers in SMP Negeri 1 Anjir Pasar do not come from educational backgrounds in the field of computers so as to cause a lack of understanding of functions the use of information and communication technology as a learning facility and as a means of supporting learning in class or as an administrative aid such as making learning implementation plans (RPPs), syllabi and evaluating student learning outcomes. The purpose of this community service activity is that partners can understand and have skills in utilizing information technology facilities as a learning tool and as a support for teacher competence in the implementation of the 2013 curriculum. The method of implementing activities is through material presentation and demonstration of the use of information technology facilities as learning media and as supporting facilities for teacher competence in implementing the 2013 curriculum.